2006
DOI: 10.3917/nqf.251.0004
|View full text |Cite
|
Sign up to set email alerts
|

De l’affaire du voile à l’imbrication du sexisme et du racisme

Abstract: Nouvelles Questions Féministes aborde ici une question centrale pour la recherche et la lutte féministes : l'imbrication des divers systèmes d'oppression. La nécessité de monter deux numéros sur cette question (le suivant paraîtra à la fin de l'année) nous a été en quelque sorte imposée par le débat qu'a suscité « l'affaire du foulard » en France et la mise en place d'une loi interdisant aux élèves de porter tout signe religieux « ostentatoire » dans les écoles publiques. Sous une pression politique et médiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Second, one finds the construction of Europe and Christianity as exempt from sexism. Although gender equality is indeed a declared priority of European instances (European Union Commission, n.d.), the phenomenon at hand can be characterized by the construction of gender equality as solely or primarily European and Western, and of Europe as comparatively virtuous on this front (Akkerman, 2015;Benelli et al, 2006). In this context, sexual violence in racialized communities is depicted as a reflection of immigrants' culture, whilst overlooking the cultural aspects of sexual violence when perpetrated by Western men (Volpp, 2001).…”
Section: Anti-sexism To Justify Anti-islam Stancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, one finds the construction of Europe and Christianity as exempt from sexism. Although gender equality is indeed a declared priority of European instances (European Union Commission, n.d.), the phenomenon at hand can be characterized by the construction of gender equality as solely or primarily European and Western, and of Europe as comparatively virtuous on this front (Akkerman, 2015;Benelli et al, 2006). In this context, sexual violence in racialized communities is depicted as a reflection of immigrants' culture, whilst overlooking the cultural aspects of sexual violence when perpetrated by Western men (Volpp, 2001).…”
Section: Anti-sexism To Justify Anti-islam Stancesmentioning
confidence: 99%
“…To be sure, individuals (and political actors) may well differ in their conception of gender rights or even have only a vague idea of what gender equality or even gender should mean (i.e., conceptualize gender as binary or not). However, they also share the view that gender issues are more advanced in the West and that the West should be the single model for women's emancipation (Benelli et al, 2006;Delphy, 2006;Duits & van Zoonen, 2006;Farris, 2017;Fernandez, 2009;Gianettoni & Roux, 2010;Howard, 2012).…”
Section: Anti-sexism To Justify Anti-islam Stancesmentioning
confidence: 99%
“…More generally, Helbling (2014) has demonstrated that majority attitudes are more negative towards hijabis than towards Muslims in general. Other scholars have argued that hostility towards veiled women is the gendered aspect of Islamophobia, and that it can be explained by stereotypes linked to the post-9/11 context (Amiraux 2007;Chakraborti and Zempi 2012) or to a particular conception of laicity in which the hijab is constructed as a threat to the latter and to republican values such as gender equality (Benelli et al 2006).…”
Section: The Hijab In the Westmentioning
confidence: 99%
“…Force est de constater que les témoignages obtenus confirment l’existence d’une discrimination, à la fois perçue, mais également vécue, envers les répondantes. En effet, on peut dire que cette situation sociale désavantageuse vécue par les femmes musulmanes qui portent le hijab peut se comprendre par le déploiement d’une double discrimination, fondée à la fois sur la religion et sur le genre (Benelli, Hertz, Delphy, Hamel, Roux et Falquet, 2006). L’expérience de la discrimination peut grandement influencer le rapport d’une femme musulmane portant le hijab dans son appréciation de la laïcité et ainsi contribuer à orienter son parcours professionnel.…”
Section: Un Contexte Défavorable Qui Fragilise Un Positionnement Pragmatiqueunclassified